The impact of microcredit program on women empowerment: Evidence from Bangladesh - Nessa, Tasqurun; Ali, Jamal; Abdul Hakim, Roslan (Ontario International Development Agency, 2012)
The empowerment of women is one of crucial development issues.This is due to the fact that women appear to form the largest of the poor and vulnerable group.In this regards, microcredit program has been argued to be potentially effective as a tool for poverty alleviation and lifting the poor, particularly women, out of poverty.The impact of microcredit program, however, is not limited to improving income of poor women.What is more important is that microcredit program has received widespread recognition as a viable strategy for empowerment of women, i.e. greater capabilities, choices and freedom in decision making.The objective of this paper is to examine the impact of microcredit program on women empowerment.Towards this end, we perform regression analysis based on a sample of 600 poor women in eight districts of Rajshahi Division, Bangladesh.Five dimensions of empowerment are used to arrive at an aggregate index of empowerment.These dimensions are: (a) economic decision making, (b) household decision making, (c) freedom of movement, (d) ownership of property, and (e) political and social awareness.The aggregate measure of empowerment is regressed against the explanatory variables, which is participation in microcredit program as well as other control variables. We also perform regression analysis for each dimension of empowerment against the explanatory variables to examine in greater details on the impact of microcredit program on each dimension of empowerment. Our finding shows that participation in microcredit program is consistently significant in explaining the aggregate measure of empowerment, as well as in explaining each dimension of empowerment. Based on the results of our study, it can be concluded that empowerment of poor women in Bangladesh can be significantly improved by encouraging them to participate in microcredit programs.